2002
DOI: 10.1002/j.0022-0337.2002.66.5.tb03542.x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Patient Records for Dental School Clinics: More Than Paperless Systems

Abstract: The Electronic Patient Record (EPR) or "computer-based medical record" is defined by the Patient Record Institute as "a repository for patient information with one health-care enterprise that is supported by digital computer input and integrated with other information sources." The information technology revolution coupled with everyday use of computers in clinical dentistry has created new demand for electronic patient records. Ultimately, the EPR should improve health care quality. The major short-term disad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 9 publications
0
27
0
3
Order By: Relevance
“…Atkinson et al have reported that EMRs support clinical decision-making; this information developed for medical clinics provide treatment suggestions based on the patient's signs, symptoms and clinical data. This system can be used to advise students and faculty of evidence-based clinical practice guidelines for various clinical situations and Electronic data interchange, including data sharing with other health professionals [8]. Williams et al also showed the potential role of EMR systems on enhancement of healthcare delivery and facilitation of decision-making processes [3].…”
Section: Discussionmentioning
confidence: 99%
“…Atkinson et al have reported that EMRs support clinical decision-making; this information developed for medical clinics provide treatment suggestions based on the patient's signs, symptoms and clinical data. This system can be used to advise students and faculty of evidence-based clinical practice guidelines for various clinical situations and Electronic data interchange, including data sharing with other health professionals [8]. Williams et al also showed the potential role of EMR systems on enhancement of healthcare delivery and facilitation of decision-making processes [3].…”
Section: Discussionmentioning
confidence: 99%
“…1 The evolution of information systems and increased use of computers in clinical dentistry has placed more emphasis on the use of patient electronic health records (EHRs). 2 A literature review by Hayrinen et al 3 provided an EHR classification based on the International Organization for Standardisation classification, and highlighted the need for common terminology, especially when defining EHRs. Their paper defined an EHR as a repository of patient data in digital form, securely stored and transferable, made accessible upon request by different users with appropriate authorisation, and containing multilevel information for the efficient provision of integrated quality healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Benefits of EHRs in clinical facilities can include improved record control, efficient documentation, storage and access to patient data, and improved information for clinical management with quality data for appraisal of patient care. 2 However, there are many different EHR systems, and this plethora of record types has caused confusion. This is especially true in the dental arena, which is a primary care system that collects huge amounts of data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Обсуждаются его недостатки, предлагаются варианты улучшения. Профессора стоматологии должны разработать более общую запись со стандартными диагностическими кодами и клиническими протоколами, чтобы сделать электронную карту более полезной для клинического приема и улучшить качество медицинской помощи [39].…”
unclassified